Quality improvement and storage study of salted and dried siganid (Theuthis tarus) - Munar, Joan I.; Acevedo, Teresita P. (1984.)
This study aimed to improved the quality of salted and dried siganid (Theuthis jarus) and to study its storage behavior. It was found that the best treatment for the product prior to drying was soaking in 8% brine for 30 minutes. The Bureau of Energy Development (BED) solar driers were used in this study. With a dry bulb temperature rang of 47 - 52°C, a wet bulb temperature range of 38 - 48°C, and a relative humidity condition of 55 - 100, the product dried at a constant rate of 2.27 gms. H2O/gm. solid/hour for the first hour, then a decreasing rate followed until the 12th hour wherein the equilibrium moisture content of 14% was attained. The optimum moisture content for the product was found to be 14 - 16%, with the product exhibiting the desired attributes of a dry appearance, golden brown color, characteristic odor, crispy texture and just right saltiness. The product exhibited a sigmoidal -shaped sorption isotherm curve. It exhibited a higroscopic nature when exposed to high relative humidity conditions and its maximum stability occurred at 20 - 70% RH. The critical moisture content f the product was determined to be 31.6%, at which point, the product appeared slightly moist, reddish brown, with slightly off-odor, chewy texture and bitter aftertaste. This was observed to have occurred on the 7th week of storage. The calculated maximum allowable water vapor transmission rate (WVTR) for the product was 60.80 gm./24 hrs./m^2/ Medium and high density polyethylene bags are recommended for packaging of the product.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Dried fish -- Philippines